An analysis of the surface geometric structure and geometric accuracy of cylindrical gear teeth manufactured with the direct metal laser sintering (DMLS) method - Małgorzata Pisula, Jadwiga (Strojniški vestnik, 2019)
This paper presents findings concerning the accuracy of the geometry of cylindrical spur gear teeth manufactured with the direct metal laser sintering (DMLS) method. In addition, the results of the evaluation of the tooth surface geometric structure are presented in the form of selected two-dimensional and three-dimensional surface roughness parameters. An analysis of the accuracy of the fabricated gear teeth was performed after gear sand-blasting and gear tooth milling processes. Surface roughness was measured before and after sand-blasting and gear tooth milling. The test gear wheel was manufactured from GP1 high-chromium stainless steel on an EOS M270 machine.
Keywords: cilindrični čelni zobniki; cylindrical spur gears; direct metal laser sintering method; geometric accuracy; geometrijska struktura površine; geometrijska točnost; postopek neposrednega laserskega sintranja kovin; surface geometric structure